A study of the attitude of generation z to cross-cultural interaction in business - Lifintsev, Denys; Fleșeriu, Cristina; Wellbrock, Wanja (Information & Media, 2019)
Background and Purpose: In a digitally globalized world cross-cultural interaction in social and business environment has become more widespread than ever before. The purpose of this paper is to explore the attitude of Generation Z representatives to different aspects of cross-cultural interaction. Design/Methodology/Approach: We used an online questionnaire to collect data for our study. A sample of 324 young adults from three countries: Germany (n=113/34.9%), Romania (n=107/33.0%) and Ukraine (n=104/32.1%) participated in the online survey. The sample consists of university students aged less than 23 years to match the criteria of being representatives of Generation Z. Different statistical tools were used to check the hypotheses. Results: The results of the study indicate that Generation Z representatives consider cross-cultural communication skills as highly important both in their private and business life. The main motivation factors to work in a multicultural business environment have been identified as well as major barriers for effective cross-cultural interaction. Conclusion: This paper illustrates that Gen Zers are willing to work in a multicultural business environment; moreover it can give them additional motivation. This trend along with ongoing processes of globalization and digitalization fosters further interconnection of countries and regions of the world, making cross-cultural communication and cross-cultural management techniques even more important.